Essential structure of orexin 1 receptor antagonist YNT-707, Part IV: The role of D-ring in 4, 5-epoxymorphinan on the orexin 1 receptor antagonistic activity. Issue 18 (15th September 2019) - Saitoh, Tsuyoshi; Seki, Kazunori; Nakajima, Ryo; Yamamoto, Naoshi; Kutsumura, Noriki; Nagumo, Yasuyuki; Irukayama-Tomobe, Yoko; Ogawa, Yasuhiro; Ishikawa, Yukiko; Tanimura, Ryuji; Yanagisawa, Masashi; Nagase, Hiroshi
Graphical abstract: Abstract: The orexin 1 receptor (OX1 R) antagonists carrying a morphinan skeleton such as YNT-707 (2 ) and YNT-1310 (3 ) showed potent and extremely high selective antagonistic activity against OX1 R. In the course of our study of the essential structure of YNT-707 for high binding affinity against OX1 R, we prepared derivatives of 2 without the D- and 4, 5-epoxy rings to clarify the roles of these structural determinants toward OX1 R antagonistic activity. The D- and 4, 5-epoxy rings played important roles for the active orientation of the 17-sulfonamide and 6-amide side chains. Finally, we identified the simple structure required for selective OX1 R antagonistic activity in the complex morphinan skeleton, which is expected to be a useful scaffold for further design of OX1 R ligands.